1967
DOI: 10.2134/agronj1967.00021962005900060006x
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of a Chlorinated Pyridine Phytotoxicity to Robinia pseudoacacia1

Abstract: Soil factors influencing phytotoxicity of the specific nitrification inhibitor, 2‐chloro‐6‐(trichloromethyl) pyridine, N‐Serve, was determined with a Typic Quarzipsamment, Eufaula sand, for Robinia pseudoacacia L. Narrow C:N ratio, 2.88% N, soil organic matter amendment, and increased temperatures to 38 C increased N‐Serve effectiveness. Soil sterilization treatment reduced N‐Serve activity. A highly active form of this pyridine accumulated in black locust foliage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1970
1970
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…The roots were stubby and club-like with swellings, particularly just behind the root tips, compared with the normal more fibrous root system of plants with 0 to 3 ppm of N-Serve. The effects of N-Serve on the growth of the shoots and roots of soybeans were very similar to those described previously for alfalfa (4) and black locust (3,6).…”
Section: Resultssupporting
confidence: 83%
“…The roots were stubby and club-like with swellings, particularly just behind the root tips, compared with the normal more fibrous root system of plants with 0 to 3 ppm of N-Serve. The effects of N-Serve on the growth of the shoots and roots of soybeans were very similar to those described previously for alfalfa (4) and black locust (3,6).…”
Section: Resultssupporting
confidence: 83%
“…There are indications that nitrapyrin may be more effective in controlling nitrification in soils with higher clay contents than in soils with lower clay contents (Bundy and Bremner, 1973). Some authors (Geronimo et al, 1973;Goring, 1962;Prasad, 1976;Rieck and Lynd, 1967;Touchton et al, 1978a) have reported differences in nitrification or crop response among soils with various pH values when equal rates of N and nitrapyrin were applied to each soil. However, with one exception, soil pH was not the primary variable investigated, and the difference in nitrification or crop response among soils was generally not attributed to the possible effect of pH on the loss of nitrapyrin from the soil.…”
mentioning
confidence: 99%
“…Many researchers have reported toxic effects of nitrapyrin on crops (13)(14)(15)(16)(17). Onions (Allium cepa L.) grown in soil treated with captan showed greatly restricted dry mass accumulation (18).…”
Section: Introductionmentioning
confidence: 99%